CAUSES AND EFFECTS OF THE BETTER HEALTH QUALITY IN PRIVATE HOSPITALS AGAINST PUBLIC HOSPITALS IN KAJIADO COUNTY - Nkirrmpai, David T.; Waweru, Mr. Alicadius (Journal of Public Policy and Administration, 2017)
Purpose: To assess the causes and effects of the better health quality in private hospitals against public hospitals in Kajiado County. Methodology: The study utilized a descriptive research design. Findings: Results indicated that a positive and significant correlation exists between infrastructure, remuneration, leadership and governance, human resource skills, training and level of health services. This implies that a positive change in infrastructure, remuneration, leadership and governance, human resource skills and training is associated with a positive change in level of health service delivery. Unique contribution to theory, practice and policy: The study highlighted the key areas of concern that lead to differences in the provision of health services between the public and private hospitals. The study made recommendations on effective and sustainable health service delivery and its management methods. Undeniably such recommendations could inform policy formulations in the various counties in the country in general because they are originated through valid research data. The findings in this study should contribute to body of knowledge that could be referred to as relevant material in reference to health provisions requirements of Vision 2030 and the realization of the MDGs.